Effect of Salinity Stress on Tomato (Lycopersicon Esculentum L.) and Mitigation Strategies - Sora, Shamil Alo; Saketa, Wakuma Merga; Yami, Abera Seboka (International Journal on Food, Agriculture and Natural Resources, 2023)
Tomato (Lycopersicon esculentum L.) belongs to the Solanaceae family. It is a crop of immense economic importance worldwide and salinity is one of the major abiotic factors limiting it's production and productivity globally. The amount of irrigation water and their evapotranspiration is the main reason that causes salinization. Salinity is an abiotic stress that affects agriculture by severely impacting crop growth and, consequently, final yield. Considering that sea levels rise at an alarming rate over year, it is clear that salt stress constitutes a top-ranking threat to agriculture. Among the economically important crops that are sensitive to high salinity is tomato one that is more affected by salt stress. Si plays the beneficial role of the quasi-essential metalloid silicon (Si), which increases the vigor and protects plants against a biotic stresses. The use of silicon fertilization can be used as sustainable practices in agricultural production to increase yield and quality of plants. Silicon fertilization also plays role in plant protection against various range of exogenous stresses especially, under changing environment. The use of appropriate irrigation method, amount and water quality to minimize the risk of salt accumulation around root zone of plants. Different plant growth regulators and amino acids could also play a great role in increasing yield and growth of tomato under salt stress.